A Comparison Between Chemo-Radiotherapy Combined With Immunotherapy and Chemo-Radiotherapy Alone for the Treatment of Newly Diagnosed Glioblastoma: A Systematic Review and Meta-Analysis - Lara-Velazquez, Montserrat; Shireman, Jack M.; Lehrer, Eric J.; Bowman, Kelsey M.; Ruiz-Garcia, Henry; Paukner, Mitchell J.; Chappell, Richard J.; Dey, Mahua (Frontiers in Oncology, 2021)
Background: Immunotherapy for GBM is an emerging field which is increasingly being investigated in combination with standard of care treatment options with variable reported success rates. Objective: To perform a systematic review of the available data to evaluate the safety and efficacy of combining immunotherapy with standard of care chemo-radiotherapy following surgical resection for the treatment of newly diagnosed GBM. Methods: A literature search was performed for published clinical trials evaluating immunotherapy for GBM from January 1st 2000 to October 1st 2020 in PubMed and Cochrane using PICOS/PRISMA/MOOSE guidelines. Only clinical trials with 2 arms (combined therapy vs. control therapy) were included. Outcomes were then pooled using weighted random effects model for meta-analysis and compared using the Wald-type test. Primary outcomes included 1 year-overall survival (OS) and progression-free survival (PFS), secondary outcomes included severe adverse events (SAE) grade 3 or higher. Results: Nine randomized phase II and/or III clinical trials were included in the analysis, totaling 1239 patients. The Meta-analysis revealed no statistically significant differences in group’s 1-year OS [80.6% (95% CI: 68.6%- 90.2%) vs. 72.6% (95% CI: 65.7%-78.9%), p=0.15] or in 1-year PFS [37% (95% CI: 26.4%-48.2%) vs. 30.4% (95% CI: 25.4%-35.6%) p=0.17] when the immunotherapy in combination with the standard of care group (combined therapy) was compared to the standard of care group alone (control). Severe adverse events grade 3-5 were more common in the immunotherapy and standard of care group than in the standard of care group (47.3%, 95% CI:20.8-74.6%, vs 43.8%, 95%CI: 8.7-83.1, p=0.81), but this effect also failed to reach statistical significance. Conclusion: Our results suggests that immunotherapy can be safely combined with standard of care chemo-radiotherapy without significant increase in grade 3-5 SAE, however there is no statistically significant increase in overall survival or progression free survival with the combination therapy.